Survey Tingkat Percaya Diri Pelajar Putri dalam Ekstrakurikuler Pencak Silat di SMK Se-Kabupaten Karawang (Study di SMKN 1 Karawang) - Apriyani, Eka; Kusuma Yuda, Aria; Sumarno, Ardawi (Universitas Singaperbangsa, 2022)
This research aims to find out how much confidence level students have in participating in pencak silat extracurricular activities at State Vocational Schools in Karawang Regency (study at SMK Negeri 1 KARAWANG) based on the factors of belief in their own abilities, optimism, responsibility, objective and rational. The subjects in this research were female students who took part in pencak silat extracurriculars. The data collection technique used in this research used a questionnaire. The method used is a survey, while the data collection technique uses a questionnaire, the questionnaire in this research is in the form of a Likert scale. The results of this research reveal the condition of the level of self-confidence of extracurricular pencak silat participants in Karawang Regency which is stated in the very low category with a percentage of 5%, in the low category with a percentage of 30%, in the medium category with a percentage of 35%, in the high category with a percentage of 18%, in the category very high with a percentage of 13%.